2020
DOI: 10.1007/s10792-020-01503-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of ozonized oil and a combination of tobramycin/dexamethasone eye drops in the treatment of viral conjunctivitis: a randomized clinical trial

Abstract: Purpose To determine whether topical tobramycin 0.3%/dexamethasone 0.1% plus ozonized oil eye drops reduces clinical signs and infectious viral titers of presumed viral conjunctivitis more than tobramycin/dexamethasone eye drops alone. Methods Prospective, single-blind, randomized, parallel-groups trial. Eighty patients with a clinical diagnosis of presumed viral conjunctivitis were randomizedly divided into two treatment groups: a study group and a control group, 40 for each group. Patients in the study group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The antiseptic and antiviral activity of ozonized oil in liposomes are well known, and its safety has been assessed in vitro and in vivo [28] . Looking at our results, we might guess that the antimicrobial activity lag was due to an inadequate concentration of the ophthalmic solution that did not reach the MIC and to the presence of liposomes that allow a gradual effect.…”
Section: Discussionmentioning
confidence: 99%
“…The antiseptic and antiviral activity of ozonized oil in liposomes are well known, and its safety has been assessed in vitro and in vivo [28] . Looking at our results, we might guess that the antimicrobial activity lag was due to an inadequate concentration of the ophthalmic solution that did not reach the MIC and to the presence of liposomes that allow a gradual effect.…”
Section: Discussionmentioning
confidence: 99%
“…The ozone contained in Ozodrop ® has a direct cytotoxic effect on pathogens such as bacteria, through oxidation, leading to the lysis and decay of pathogenic organisms. Moreover, it has been suggested that the use of these drops may adapt the eye tissue to them and thus make the eye surface resistant to extrinsic free radicals [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, liposomal ozonated oil has shown antiseptic and reparative properties and can be proposed for the prevention and treatment of acute and chronic local infections, as an alternative to topical antimicrobial agents, on account of its antibacterial, antifungal and antiviral properties. [4][5][6] Liposomal ozonated oil can therefore be a useful alternative for countering the widespread and indiscriminate use of antibiotics, which has led to the emergence of bacterial resistance, especially in Staphylococci sp. Moreover, topical ozonated oil was seen to accelerate acute cutaneous wound repair in Guinea pig models by promoting collagen synthesis and fibroblast proliferation at the injury site.…”
Section: Discussionmentioning
confidence: 99%
“…Eye drops containing ozone were recently used in the management of ocular surface infection caused by bacteria, viruses and fungi, [4][5][6] and a specific formulation containing liposomal ozonated sunflower oil (Ozodrop ® , FB Vision, San Benedetto del Tronto, Italy) that is well tolerated by the conjunctival mucosa and ocular surface has been developed. 7 The most frequently diagnosed anterior segment conditions are uveitis, corneal abrasion, corneal ulcer, Meibomian gland dysfunction, dry eye, blepharitis, punctate epithelial erosions, conjunctivitis and epidemic keratoconjunctivitis.…”
Section: Introductionmentioning
confidence: 99%